Planing of land use of structural elements of ecological network at local level - Tretiak, V.; Hun'ko, L. (Land Management, Cadastre and Land Monitoring, 2017)
Land Management projecting of structural elements of land use of the ecological network on the territory of the village council begins with ecological and landscape micro zoning of the territory of village council, held during the preparatory work for the drafting of land and are finished by the formation of environmentally homogeneous regions, to which the system components of ecological network are tied, as well as environmental measures in the form of local environmental restrictions (encumbrances) in land usage and other natural resources. Additionally organization and territorial measures are projected that increase the ecological sustainability of the area: key, binders, buffer areas and renewable ecological network.The regional scheme of ecological network is intended for usage while projecting of creation of new territories that fall under special protection, for defining the tasks as for changing the category of land in the land use planning documents, for development of specifications regarding the reproduction of natural systems on conservation ready lands withdrawn from agricultural use, for accounting the problems of formation the areas of ecological network in forest management and land management projects, while development of the projects of areas organization of natural - reserve fund, in the definition of wetlands of international importance, in determining the habitats of various plants and animals of various categories of protection in accordance with international conventions and national laws - regulations, in planning targeted actions in the conservation of landscape and biological diversity.The main stages of designing local ecological network are:• inventory and identification of rights for land and other natural resources, drawing created territories and objects of natural reserve fund and other areas of natural systems on the planning and cartographic materials, which are under special protection;• rationale of creating additional territories and objects of nature preserves and other areas of valuable natural systems, which are under special protection as a key and defining the boundaries of renewable, buffer and connecting areas for the providing of the formation of the ecological network as a unified spatial system of ecological frame of conservation land using cartograms of agro-industrial groups of soils and terrain rural area (village) councils;• development of registers of territorial restrictions (encumbrances) in land use and other natural resources in the area and objects of nature preserves and other areas under special protection, recovery, binding and buffer areas of ecological network, as well as proposals for regime change of land use and use of other natural resources;• coordination with the General scheme and regional schemes of eco network about limits of areas of its components in adjacent areas, with Pan-European Ecological Network taking into account modern state, public and private interests, identifying promising areas to ensure conservation and rational management of landscapes and other natural systems, other objects and territories.According to the Law of Ukraine "On Land Management", there is not any particular type of documentation on land use, as for designing structural elements of econet, therefore there is a need in justification of features of such projecting and its legislative resolution. On the basis of land management projects on the formation of components of the ecological network in the context of rural councils it’s possible to determine the boundaries of the restriction (encumbrances) zones, its area and draw their registry and regulations of land use to meet the requirements of rational land use and protection, preservation of natural diversity of landscapes, environment, maintaining ecological balance. Keywords: land use, ecological networks, landscapes, natural resources, the key area.